Power supplies dynamic redistribution’s for electric system with dispersed generation - B. A. Kosarev; G. A. Koschuk; V. K. Fedorov; L. G. Polyntsev (Омский научный вестник)
The article concerns design of electric system with dispersed generation, more precisely, functional location of energy generation units — transmission losses relationship. Electrical load centers are the optimal locations of energy generation units, but time-varying loads shift them and transmission losses increase. The purpose of the article is development of an algorithm and the program of power supplies dynamic redistribution’s for the electric system with dispersed generation that reduce transmission losses. Power supplies dynamic redistribution’s is achieved by the creation of a virtual electric system with the possibility of redistribution over electrical load centers of energy generation units. Virtual electric system is organized on the basis of cellular communication and central computer (smart grid). The algorithm is realized in the computer-aided design MathCAD. Using this program, the calculation of the electric system of an industrial microdistrict of the city with distributed generation was performed. As a result of the calculations, cartograms of electrical loads are constructed and the loss of electric energy in distribution lines is estimated. The calculation results show a significant reduction in losses in distribution lines when using distributed generation with dynamic redistribution of power sources.